South Korean Firms’ operation in Vietnam and some implications for Expansion strategy = Hoạt động của các công ty Hàn QUốc tại Việt Nam và một số gợi ý cho chiến lược mở rộng - Kim, Wooseok (2020)
During the global financial crisis, Vietnam experienced slowing growth. Vietnam's growth potential is drawing attention as the external economic environment is becoming favorable, such as the recent increase in FDI inflows, the signing of bilateral and multilateral FTAs, and the establishment of the ASEAN Economic Community (AEC). Also, positive improvements in domestic conditions, such as political stability, abundant low-income labor, and a population of nearly 100 million, increased interest among major investors in Vietnam, and increased FDI inflows. In particular, the FDI was introduced in 2015, the largest amount ever, and the economic growth rate was 6.68 percent, the level before the global financial crisis. On the other hand, Vietnam's business environment is not only positive, considering that negative factors persist, such as corruption, lack of skilled manpower and inefficiency in state-run companies. The Doing Business Assessment, which provides a comparative analysis of each country's business environment